2023
DOI: 10.1093/procel/pwad032
|View full text |Cite
|
Sign up to set email alerts
|

Innovative insights into extrachromosomal circular DNAs in gynecologic tumors and reproduction

Abstract: Originating but free from chromosomal DNA, extrachromosomal circular DNAs (eccDNAs) are organized in circular form and have long been found in unicellular and multicellular eukaryotes. Their biogenesis and function are poorly understood as they are characterized by sequence homology with linear DNA, for which few detection methods are available. Recent advances in high-throughput sequencing technologies have revealed that eccDNAs play crucial roles in tumor formation, evolution, and drug resistance as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…It is hypothesized that eccDNAs in circulation may complement miRNA and linear DNA, potentially serving as a means for disease diagnosis and intercellular communication ( Kumar et al, 2017 ). Unfortunately, Circle_finder cannot discriminate between eccDNA and chromosomal segmental tandem repeats ( Zhao et al, 2023 ; Wu et al, 2024 ). iii) Circle-Map.…”
Section: Computational Identification and Prediction For Eccdnamentioning
confidence: 99%
See 2 more Smart Citations
“…It is hypothesized that eccDNAs in circulation may complement miRNA and linear DNA, potentially serving as a means for disease diagnosis and intercellular communication ( Kumar et al, 2017 ). Unfortunately, Circle_finder cannot discriminate between eccDNA and chromosomal segmental tandem repeats ( Zhao et al, 2023 ; Wu et al, 2024 ). iii) Circle-Map.…”
Section: Computational Identification and Prediction For Eccdnamentioning
confidence: 99%
“…Furthermore, results such as eccDNA containing oncogenes ( Kalavska et al, 2018 ; Gu et al, 2020 ; Li et al, 2022 ; Li et al, 2022 ) and being associated with drug resistance ( Alt et al, 1978 ; Kaufman et al, 1979 ; Haber and Schimke, 1981 ; Kaufman et al, 1981 ; Shoshani et al, 2021 ) have highlighted the possible use of eccDNA in tumor therapy and monitoring. Freshly, several studies have suggested the use of eccDNA for the diagnosis, treatment, and monitoring of gliomas ( Li et al, 2023 ), gynecologic tumors ( Wu et al, 2024 ), and genitourinary disorders ( Lv et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation